DETECTION OF TUBERCULOUS MYCOBACTERIA IN THE BLOOD OF PATIENTS WHEN SUSPECTING TUBERCULOUS SEPSIS - V. N. Zimina; O. E. Mikova; D. A. Oborin; S. Yu. Degtyareva; I. B. Viktorova (Туберкулез и болезни лёгких)
The increase in HIV patients manifesting clinical signs of sepsis requires up-to-date, rapid and reliable techniques for etiologic diagnostics.The analysis has included 53 publications related to various aspects of tuberculous bacteriemia, resources for its detection and their efficiency. According to the publications tuberculous mycobacteria in blood can be detected in HIV-positive patients with severe immune suppression (CD4: 17-18 cells/mcl) and presence of the following clinical and laboratory and X-ray signs: fever, severe anemia, paratracheal lymphoadenopathy, miliary dissemination. It is feasible to test the blood in order to detect tuberculous mycobacteria only in the very ill HIV positive patients in whom tuberculosis is suspected and it is impossible to collect sputum and there are no obvious signs of pulmonary lesions.The presence oftuberculous mycobacteria in blood isrelated to the high mortality level (up to 60%) and the immediate prescription of anti-tuberculosis therapy can reduce it. Antiretroviral therapy can reduce the chances of tuberculous sepsis development. Development and optimization of test systems for rapid detection of DNA of tuberculous mycobacteria in blood can be fairly promising for the diagnostics of the urgent tuberculosis.